Dispersal and water age of the plumes from the four outlets of the Pearl River during the dry winter - Guang Zhang; Pengpeng Hu; Suan Hu; Yuren Chen; Junpeng Zhao; Chunlei Ma; Heng Zhang; Wenping Gong (Marine Pollution Bulletin, 2026)

Treatment patterns and outcomes of second/third-line therapy in advanced non-small cell lung cancer with actionable genomic alterations (RECAP) - Hanxiao Chen; Xiangjiao Meng; Ling Cai; Wei Lei; Yu Tang; Xi Shi; Leilei Ma; Jun Zhao (Clinical & Experimental Metastasis, 2026)
Treatment choices for metastatic non-small-cell lung cancer (NSCLC) after first-line targeted therapy progression are heterogeneous. This study aimed to characterize real-world treatment patterns and outcomes of advanced NSCLC harboring actionable genomic alterations (AGAs) in second- (2 L) or third-line (3 L) settings. This retrospective cohort study across six Chinese centers included stage IV NSCLC patients with confirmed AGAs. Therapies were divided into six categories: targeted monotherapy (T), targeted combinations (T+), chemotherapy monotherapy (C), chemotherapy combinations (C+), anti-angiogenic monotherapy (A), and other regimens (O). The primary outcome was the treatment pattern. Secondary outcomes included biomarker testing and effectiveness. A total of 658 patients were enrolled, with the majority harboring EGFR mutations ( n = 590, 89.7%). In the 2 L-enrolled group ( n = 602), T use declined from 75.3% in the 1 L setting to 49.3% in 2 L, while utilization of A + C increased to 16.5%. Within the EGFR-mutant subgroup, therapeutic sequences were highly dependent on 1 L TKI generation and T790M resistance status. Over half (51.1%) of T790M-negative patients continued T in 2 L following progression on 1 L first- or second-generation TKIs. Among the 3 L-enrolled patients ( n = 56), A + C (35.7%) and C (14.3%) were predominant. The overall median real-world progression-free survival for the 2 L-enrolled group was 7.4 months in the 2 L setting (7.5 months for the EGFR-mutant subgroup) and 5.4 months in 3 L. This multicenter real‑world cohort predominantly comprised patients with EGFR‑mutant NSCLC, with smaller numbers of other AGA subtypes. Targeted therapies remain the cornerstone of later-line advanced NSCLC management. The prevalent real-world reliance on continued TKI therapy, even in T790M-negative patients, highlights the clinical dilemma of limited post-resistance options and the need to integrate emerging novel therapeutics.

Redistributing organic fertilizer from maize to wheat season improves soil functionality, microbial ecological networks, and annual crop yields in wheat–maize rotations - Xiaoying Chen; Zishuang Li; Huanyu Zhao; Yan Li; Jianlin Wei; Lei Ma; Fuli Zheng; Deshui Tan (Applied Soil Ecology, 2026)

Managing groundwater extraction to desalinate residual saltwater in coastal subsurface reservoirs: Transient behaviors and environmental implications - Yunhai Fang; Lei Ma; Tianyuan Zheng; Jian Luo; Huan Wang; Jiazhong Qian; Xilai Zheng; Marc Walther (Advances in Water Resources, 2025)